5p-3=2p+24

Simple and best practice solution for 5p-3=2p+24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5p-3=2p+24 equation:


Simplifying
5p + -3 = 2p + 24

Reorder the terms:
-3 + 5p = 2p + 24

Reorder the terms:
-3 + 5p = 24 + 2p

Solving
-3 + 5p = 24 + 2p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-2p' to each side of the equation.
-3 + 5p + -2p = 24 + 2p + -2p

Combine like terms: 5p + -2p = 3p
-3 + 3p = 24 + 2p + -2p

Combine like terms: 2p + -2p = 0
-3 + 3p = 24 + 0
-3 + 3p = 24

Add '3' to each side of the equation.
-3 + 3 + 3p = 24 + 3

Combine like terms: -3 + 3 = 0
0 + 3p = 24 + 3
3p = 24 + 3

Combine like terms: 24 + 3 = 27
3p = 27

Divide each side by '3'.
p = 9

Simplifying
p = 9

See similar equations:

| 280=(18-x)x+20x | | 104=38-3x | | x+50+10+x=180 | | (15x-23)+(8x+12)=180 | | 65+195(x-1)=2405 | | 0.35*x+1.6=-0.5 | | -71+5x=48-2x | | 4x+12=5x+9-x+3 | | -71+5c=48-2x | | 65+195x= | | (2x+7)+32=5x-15 | | -4=-1-4 | | 2a+3b+3c=74 | | 12x-153=2x+77 | | 11(y+4)=66 | | 9x^2-6x+1=18x^2-2 | | 18-(6-10y)=4(2y-6)-8 | | -4=-4*-1 | | -8x+2y=5 | | 24a^3+3b^3= | | 4+2x-8x+10+11x=-1 | | -6x-18=33-9x | | -5y+6=-12+62 | | -5+2v=-1 | | 4/16=x/35 | | 3x+76=8x-14 | | 5(x-4)-2(x+5)=15 | | x^3-xy+y^3=1 | | x+3=2XA+7 | | 4q/7=1/5 | | 9(y+3)-5(2y-4)=47 | | 9x-116=-4x+105 |

Equations solver categories